2020
DOI: 10.3389/fmicb.2020.578009
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia psittaci Plasmid-Encoded CPSIT_P7 Elicits Inflammatory Response in Human Monocytes via TLR4/Mal/MyD88/NF-κB Signaling Pathway

Abstract: The chlamydial plasmid, an essential virulence factor, encodes plasmid proteins that play important roles in chlamydial infection and the corresponding immune response. However, the virulence factors and the molecular mechanisms of Chlamydia psittaci are not well understood. In the present study, we investigated the roles and mechanisms of the plasmid-encoded protein CPSIT_P7 of C. psittaci in regulating the inflammatory response in THP-1 cells (human monocytic leukemia cell line). Based on cytokine arrays, CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…immune response against C. psittaci infection, providing an invaluable opportunity to understand psittacosis pathogenesis. When C. psittaci invades human or animal cells or tissues, a variety of inflammatory cytokines are upregulated, particularly IL-6, IL-8, MCP-1, GM-CSF, TNF-a, and anti-inflammatory factor IL-10 (20-22), and the TLR4/Mal/MyD88/NF-kB signaling axis is activated, which contributes to the innate immune responses (23), which may play different pathogenic roles in the process of C. psittaci infection. Consistent with the previous findings, we found that levels of a variety of cytokines, such as IL-6, IL-1RN, and TNF-a, increased rapidly in the pneumonia cases, thereby accelerating the inflammatory response (24).…”
Section: Discussionmentioning
confidence: 99%
“…immune response against C. psittaci infection, providing an invaluable opportunity to understand psittacosis pathogenesis. When C. psittaci invades human or animal cells or tissues, a variety of inflammatory cytokines are upregulated, particularly IL-6, IL-8, MCP-1, GM-CSF, TNF-a, and anti-inflammatory factor IL-10 (20-22), and the TLR4/Mal/MyD88/NF-kB signaling axis is activated, which contributes to the innate immune responses (23), which may play different pathogenic roles in the process of C. psittaci infection. Consistent with the previous findings, we found that levels of a variety of cytokines, such as IL-6, IL-1RN, and TNF-a, increased rapidly in the pneumonia cases, thereby accelerating the inflammatory response (24).…”
Section: Discussionmentioning
confidence: 99%
“…In great contrast, inhibition of TLR2, MyD88, and NF-κB in HD11 cells was reported to significantly decrease IL-6 and IL-10 cytokine levels associated with significantly enhanced NO production and phagocytosis [ 307 ]. The plasmid-encoded protein CPSIT_P7 of Chlamydia psittaci was shown to induce the TLR4/Mal/MyD88/NF-κB signaling axis and orchestrate the inflammatory cytokine response [ 308 ].…”
Section: Effect Of Various Stress Factors On Nf-κb Expression and mentioning
confidence: 99%
“…Meanwhile, microorganisms such as Bacillus spp., Actinomyces spp. and even Chlamydia psittaci or Chlamydia abortus can directly or indirectly regulate the expression of host pro-inflammatory factors or important disease-related genes such as METTLE3, thus affecting the physiological and pathological processes of the host ( Pan et al., 2017 ; Chen et al., 2020a ; Gómez-García et al., 2022 ; Wang et al., 2022 ; Xu et al., 2022 ; Zhang et al., 2022b ). These previous studies will help us to conduct future research on the direction of microbial-host immune interactions in terms of how microbes and their metabolites regulate pro-inflammatory signaling pathways, and how microbes and their metabolites are involved in the regulation of signaling pathways and expression of key targets related to important diseases such as inflammation or tumours.…”
Section: Discussionmentioning
confidence: 99%